Development of a hybrid model for website functional evaluation based on ISO/IEC 25010 and SERVQUAL - Prameswari, Ardiva Putri Tava; Setyawan, Muhammad Yusril Helmi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study developed a hybrid model based on ISO/IEC 25010 and SERVQUAL to evaluate website quality holistically by combining technical dimensions and user perceptions. ISO / IEC 25010 is an international standard for evaluating the quality of software, including websites, based on technical characteristics such as Functional Suitability, Usability, Reliability, and Security. SERVQUAL, on the other hand, is used to measure quality based on user perception through five main dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This study aims to identify the gaps between user expectations and the reality of website performance by using both frameworks. The research method combines quantitative and qualitative approaches, with user surveys and direct observation as data collection tools. The results of the analysis showed that most website quality dimensions, such as Functional Suitability, Usability, Reliability, Responsiveness, and Security, were in the category of